2015
DOI: 10.1007/s11357-015-9818-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between STR autosomal markers and longevity

Abstract: Life span is a complex and multifactorial trait, which is shaped by genetic, epigenetic, environmental, and stochastic factors. The possibility that highly hypervariable short tandem repeats (STRs) associated with longevity has been largely explored by comparing the genotypic pools of long lived and younger individuals, but results so far have been contradictory. In view of these contradictory findings, the present study aims to investigate whether HUMTHO1 and HUMCSF1PO STRs, previously associated with longevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For instance, De Benedictis et al (1998) reported a significant association of >9 TH01 repeats with longevity in male Italian centenarians. Contrariwise, von Wurmb-Schwark et al (2011) were unable to replicate this result when using the same study design on a German population, just as Bediaga et al (2015) were also unable to confirm an association in a northern Spanish population. Similarly, there are conflicting reports on the association of TH01-9.3 with SIDS across European populations.…”
Section: Th01mentioning
confidence: 94%
“…For instance, De Benedictis et al (1998) reported a significant association of >9 TH01 repeats with longevity in male Italian centenarians. Contrariwise, von Wurmb-Schwark et al (2011) were unable to replicate this result when using the same study design on a German population, just as Bediaga et al (2015) were also unable to confirm an association in a northern Spanish population. Similarly, there are conflicting reports on the association of TH01-9.3 with SIDS across European populations.…”
Section: Th01mentioning
confidence: 94%
“…The main purpose of the research conducted by N.G. Bediaga et al (2015) was to show the statistically relevant association between polymorphism of hypervariable STR loci such as HUMTHO1 (THO1) and HUMCSF1PO (CSF1PO) that are used in forensic practice and longevity. In a way to study 21 autosomal STR loci polymorphisms, 304 people aged 90 and over and 516 younger controls of European origin living in northern Spain were studied.…”
mentioning
confidence: 99%